Selenium supplementation suppresses immunological and serological features of lupus in B6.Sle1b mice - Chetna Soni; Indu Sinha; Melinda J. Fasnacht; Nancy J. Olsen; Ziaur S.M. Rahman; Raghu Sinha (Taylor & Francis Group, 2019)
Systemic lupus erythematosus (SLE) is a debilitating multi-factorial immunological disorder characterized by increased inflammation and development of anti-nuclear autoantibodies. Selenium (Se) is an essential trace element with beneficial anti-cancer and anti-inflammatory immunological functions. In our previous proteomics study, analysis of Se-responsive markers in the circulation of Se-supplemented healthy men showed a significant increase in complement proteins. Additionally, Se supplementation prolonged the life span of lupus prone NZB/NZW-F1 mice. To better understand the protective immunological role of Se in SLE pathogenesis, we have investigated the impact of Se on B cells and macrophages using in vitro Se supplementation assays and the B6.Sle1b mouse model of lupus with an oral Se or placebo supplementation regimen. Analysis of Se-treated B6.Sle1b mice showed reduced splenomegaly and splenic cellularity compared to untreated B6. Sle1b mice. A significant reduction in total B cells and notably germinal center (GC) B cell numbers was observed. However, other cell types including T cells, Tregs, DCs and pDCs were unaffected. Consistent with reduced GC B cells there was a significant reduction in autoantibodies to dsDNA and SmRNP of the IgG2b and IgG2c subclass upon Se supplementation. We found that increased Se availability leads to impaired differentiation and maturation of macrophages from mouse bone marrow derived progenitors in vitro. Additionally, Se treatment during in vitro activation of B cells with anti-CD40L and LPS inhibited optimal B cell activation. Overall our data indicate that Se supplementation inhibits activation, differentiation and maturation of B cells and macrophages. Its specific inhibitory effect on B cell activation and GC B cell differentiation could be explored as a potential therapeutic supplement for SLE patients.